Blood transfusion in cardiac surgery does increase the risk of 5‐year mortality: results from a contemporary series of 1714 propensity‐matched patients. Issue 4 (2nd August 2013) - Shaw, Richard E.; Johnson, Christopher K.; Ferrari, Giovanni; Brizzio, Mariano E.; Sayles, Kathleen; Rioux, Nancy; Zapolanski, Alex; Grau, Juan B.
<x xml:space="preserve">Abstract</x> Background Studies have found that cardiac surgery patients receiving blood transfusions are at risk for increased mortality during the first year after surgery, but risk appears to decrease after the first year. This study compared 5‐year mortality in a propensity‐matched cohort of cardiac surgery patients. Study Design and Methods Between July 1, 2004, and June 30, 2011, 3516 patients had cardiac surgery with 1920 (54.6%) requiring blood transfusion. Propensity matching based on 22 baseline characteristics yielded two balanced groups (blood transfusion group [BTG] and nontransfused control group [NCG]) of 857 patients (1714 in total). The type and number of blood products were compared in the BTG. Results Operative mortality was higher in BTG versus NCG (2.3% vs. 0.4%; p < 0.0001). Kaplan‐Meier analysis of 5‐year survival demonstrated no difference between groups in the first 2 years (BTG 96.3% and 93.0% vs. NCG 96.4% and 93.9%, respectively). There was a significant divergence during Years 3 to 5 (BTG 82.0% vs. NCG 89.3% at 5 years; p < 0.007). Five‐year survival was significantly lower in patients who received at least 2 units of blood (79.6% vs. 88.0%; p < 0.0001). In multivariate Cox regression analyses, transfusion was independently associated with increased risk for 5‐year mortality. Patients receiving cryoprecipitate products had a twofold mortality risk increase (adjusted hazard ratio, 2.106; p = 0.002). Conclusion Blood transfusion, specifically cryoprecipitates, was independently associated with increased 5‐year mortality. Transfusion during cardiac surgery should be limited to patients who are in critical need of blood products.